The Influence of Work Discipline, Transformational Leadership Style, and Job Training on Employee Performance - Rosallina, Monica Nathasya; Hikmah, Khoirul (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
Currently, the ability of human resources greatly determines the success of a company in achieving its goals. The purpose of this study is to determine the influence of work discipline, transformational leadership style, and job training on employee performance at Bank Kalteng Tamiang Layang. This study used quantitative methods with an associational descriptive approach using questionnaires as a data measuring tool. The population in this study amounted to 32 employees. Sampling technique using non-probability sampling. Data analysis in this study consisted of multiple linear regression analysis and hypothesis testing using SPSS application. The results of this study are known that the work discipline variable has a significance value of 0.848. The Transformational Leadership Style variable has a significance value of 0.255. The job training variable has a significance value of 0.192. So it can be concluded that work discipline, transformational leadership style, and job training have a positive and significant effect on employee performance at Bank Kalteng Tamiang Layang.